2010
DOI: 10.2202/1935-1682.2423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Old-Age Demogrant on the Labor Supply and Time Use of the Elderly and Non-Elderly in Mexico

Abstract: This paper estimates the effect of a generous demogrant for individuals age 70 and older that started in 2001 in Mexico City on the labor supply and time use of beneficiaries and of non-elderly family members who live with them. Using a triple differences approach, I find that the program has no significant effect on the time use of eligible individuals, except for the sharp decrease in the housework participation of elderly women who live with another potential beneficiary. Individuals 60 to 69 years old chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…In these estimations, our key regressor is the interaction of the number of age-qualifying individuals in the household with the dummy for a treated locality, which captures both household eligibility for 70 y Más and variation in the amount potentially received from the program. In the literature, given that resources owned by women are often found to have different effects than those owned by men, it is standard to further control for the gender of the beneficiary, as in Bertrand, Mullainathan, and Miller (2003), Juárez (2010), and Edmonds (2006). However, for our samples of prime-age adults and adolescents, we only find significant differences in the program's effect by beneficiary's gender for boys age 12-17.…”
Section: Effects On Other Household Membersmentioning
confidence: 74%
See 1 more Smart Citation
“…In these estimations, our key regressor is the interaction of the number of age-qualifying individuals in the household with the dummy for a treated locality, which captures both household eligibility for 70 y Más and variation in the amount potentially received from the program. In the literature, given that resources owned by women are often found to have different effects than those owned by men, it is standard to further control for the gender of the beneficiary, as in Bertrand, Mullainathan, and Miller (2003), Juárez (2010), and Edmonds (2006). However, for our samples of prime-age adults and adolescents, we only find significant differences in the program's effect by beneficiary's gender for boys age 12-17.…”
Section: Effects On Other Household Membersmentioning
confidence: 74%
“…8 Other mechanisms through which non-contributory pensions end up benefiting younger individuals are the nutrition and schooling and children (Duflo 2003, Edmonds 2006, Gutierrez and Rubli 2011 and family transfers (Jensen 2004, Juárez 2009, AmuedoDorantes and Juárez 2012, Fan 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The results, available from the author, are consistent with those obtained using the IV Tobit. Reduced-form estimations including the instruments directly in the transfer equations also yield comparable results 23 .…”
Section: Additional Empirical Checksmentioning
confidence: 76%
“…Juarez (2007) …nds that the Mexico City demogrant has a negative and signi…cant e¤ect on the time devoted to housework by potential bene…ciaries, and a positive, but not signi…cant, e¤ect on their leisure hours 22 . Estimating the e¤ect of the program on other outcomes of interest, like health or mortality, is beyond the scope of this paper, but it is certainly necessary to make a broader assessment of the program.…”
Section: Resultsmentioning
confidence: 99%
“…First, government programs for the elderly that are parallel to traditional social security have recently expanded in Mexico and other developing countries, due to large fraction of individuals that do not qualify for a contributory pension. In addition to investigating the effects on the economic outcomes of the direct beneficiaries of such programs, some studies have shown that public resources paid to the elderly are shared with younger individuals through the crowding out of private transfers (Jensen (2004); Juarez (2009)), reductions in labor supply (Bertrand et al (2003); Juarez (2010)) and human capital investments (Edmonds (2006); Duflo (2003)). Second, given that eligibility for many of such programs is exclusively conditioned on age, these transfers constitute an anticipated increase in permanent income for individuals who are close to eligibility age.…”
Section: Introductionmentioning
confidence: 99%